1997
DOI: 10.1111/j.1745-4549.1997.tb00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fish Protein, Salt, Sugar, and Monosodium Glutamate on the Gelatinization of Starch in Fish-Starch Mixtures

Abstract: Differential Scanning calorimetry (DSC) was used to study the effect of fish protein, salt, sugar, and monosodium glutamate (MSG) on gelatinization of tapioca and sago starches in fish cracker mixtures. One endothermic transition was observed for fish‐starch mixtures (10–90% wet fish) if the moisture content was more than 61%. The effect of the salt on the starch gelatinization is greater than sugar and MSG. Sugar and MSG addition to the mixture had little effect on gelatinization of starch in the system. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…A portion of this waste can be used to obtain minced fish using a meat/bone separator, and the resulting product can be used as meat raw material to prepare a wide variety of products (Oliveira Filho et al, 2010). MF from marine fish has been used to produce snack fish, such as soldier croaker (Johnius soldado) (Kyaw et al, 2001), bigeye grunt (Brachydeuterus auritus) (King, 2002) snapper (Lutjanus spp), giant snakedead (Ophiocephalus micropeltes), hake (Merluccius gayi) (Rado et al, 1989), cod (Gadus morhua) (Shaltout, 1993;Cheow et al, 1999) and Siena spp (Cheow & Yu, 1997). However, studies on the use of MF from tilapia as raw material for snack preparation are not available in literature.…”
Section: Introductionmentioning
confidence: 99%
“…A portion of this waste can be used to obtain minced fish using a meat/bone separator, and the resulting product can be used as meat raw material to prepare a wide variety of products (Oliveira Filho et al, 2010). MF from marine fish has been used to produce snack fish, such as soldier croaker (Johnius soldado) (Kyaw et al, 2001), bigeye grunt (Brachydeuterus auritus) (King, 2002) snapper (Lutjanus spp), giant snakedead (Ophiocephalus micropeltes), hake (Merluccius gayi) (Rado et al, 1989), cod (Gadus morhua) (Shaltout, 1993;Cheow et al, 1999) and Siena spp (Cheow & Yu, 1997). However, studies on the use of MF from tilapia as raw material for snack preparation are not available in literature.…”
Section: Introductionmentioning
confidence: 99%
“…Cheow and Yu 5 found that 20 g kg À1 salt increased the gelatinisation temperature of ®sh±starch mixture by 4±5°C. Sugar and monosodium glutamate had little effect on gelatinisation of starch in the system.…”
Section: Introductionmentioning
confidence: 99%
“…Color and texture are the major factors responsible for the final acceptability of surimi-like products by consumers. To better suit the textural preferences of consumers, ingredients that modify the textural and water mobility properties of the surimi must be added to surimi paste (Cheow and Yu, 1997). In a composite food such as surimi, additives can modify the texture.…”
Section: Introductionmentioning
confidence: 99%